Catalyst containing Beta / Y composite molecular sieve, preparation method and application thereof, and aromatic hydrocarbon liquid phase transalkylation method
By using a catalyst containing Beta/Y composite molecular sieve and nickel, the problems of low aromatic conversion and low xylene selectivity in the liquid-phase aromatic alkyl transfer reaction are solved, and efficient xylene production is achieved.
Patent Information
- Application Number
- CN202311477446.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-11-07
AI Technical Summary
The prior art has problems in the liquid-phase aromatic hydrocarbon alkyl transfer reaction with low aromatic hydrocarbon conversion and low xylene selectivity.
A catalyst containing Beta/Y composite molecular sieve is used, which consists of Beta/Y composite molecular sieve and nickel. The mass percentage of Beta/Y composite molecular sieve is 95-99%, and the mass percentage of nickel is 1-5%. The catalyst is formed by a specific preparation method, including mixing, hydrothermal treatment and nickel precursor impregnation, to form a catalyst with high catalytic activity.
Under liquid phase reaction conditions, the catalyst has high aromatic conversion and xylene selectivity, which effectively improves the production efficiency of xylene and the purity of the product.
Smart Images

Figure CN119951572A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a catalyst containing a Beta / Y composite molecular sieve, a preparation method and application thereof, and a method for liquid-phase alkylation of aromatic hydrocarbons. Background Art
[0002] As an important organic chemical raw material, xylene has a wide range of uses in industry. It can be used as a solvent in the coating, resin, dye, ink and other industries; it can be used as a synthetic monomer or solvent in the pharmaceutical, explosive, pesticide and other industries; it can also be used as a high-octane gasoline component. The most used product in xylene is para-xylene, which can be used to produce polyester, and the demand is also increasing day by day. The main methods for producing xylene in industry include: 1) using naphtha as a raw material through a series of processes such as catalytic reforming, separation and purification to obtain xylene and other high-added products; 2) using toluene disproportionation and transalkylation technology, that is, toluene and C9 aromatics are converted into benzene and xylene under the action of a catalyst. The reaction mainly includes: toluene disproportionation reaction and transalkylation reaction. Toluene disproportionation reaction generally refers to the generation of one benzene molecule and one xylene molecule by the disproportionation reaction of two toluene molecules. Transalkylation reaction generally refers to the generation of two xylene molecules by one toluene molecule and one trimethylbenzene molecule under the action of a catalyst.
[0003] Conventional toluene disproportionation and transalkylation process technology is usually carried out at a relatively high reaction temperature (350-410°C). The materials are mixed in the gas phase and converted in contact with the catalyst. A large amount of hydrogen is usually consumed during the reaction. The target products benzene and xylene are separated from the products. The unreacted useful materials are separated and recycled for conversion. Usually, there will be excessive cracking during the reaction, resulting in aromatic losses, and a small amount of heavy aromatic by-products are produced. Since they cannot be converted, they need to be discharged, which increases energy consumption and increases production costs.
[0004] Although major foreign oil companies have developed new disproportionation and transalkylation catalysts in recent years, the energy consumption required for the operation of the equipment is still high. Therefore, it is proposed to develop liquid-phase aromatic transalkylation catalysts and process technologies to alleviate the high energy consumption of refineries in the production of xylene. Liquid-phase aromatic transalkylation technology is a process in which the reactants are mixed in liquid form and contacted with the catalyst for conversion. The reaction temperature is usually 200-330°C. It has the advantages of low energy consumption, low aromatic loss, low by-products, and high xylene selectivity. Although hydrogen is also required to participate in the reaction during the reaction, the amount used is much lower than that of the gas phase reaction. It only needs to dissolve the hydrogen in the reactants.
[0005] CN109790084A discloses a method for transalkylation of heavy aromatic hydrocarbons. + A method for producing xylene from aromatic hydrocarbons comprises: +The first feed of aromatic hydrocarbons is contacted with a catalyst under vapor phase dealkylation conditions effective in the presence of 0 wt % or more hydrogen to dealkylate a portion of the C9 + Aromatics are dealkylated to produce benzene, toluene and residual C9 + The first product of aromatics. Contains C9 + A second feed of aromatics and benzene and / or toluene is reacted with a second catalyst in an effective liquid phase C9 + contacting under transalkylation conditions so that at least a portion of the C9 + The aromatics are transalkylated and produce a second product comprising xylenes.
[0006] CN108779047A discloses a method for liquid phase aromatic hydrocarbon transalkylation, wherein the catalyst used comprises a molecular sieve having a 3-dimensional 12-membered ring skeleton structure, a molecular sieve having a 1-dimensional 12-membered ring skeleton structure, and a pore channel of at least The method includes performing a transalkylation process wherein at least a portion of the feed to the transalkylation process is in a liquid phase, and some embodiments include a liquid phase transalkylation process for a naphthalene-containing feed stream.
[0007] CN109803944A discloses a method for disproportionation and transalkylation of heavy aromatics. The method comprises: (a) contacting a feedstock containing toluene with a first catalyst under effective gas-phase toluene disproportionation conditions to disproportionate the toluene and produce a first product including benzene, unreacted toluene and more p-xylene than the equilibrium amount; and (b) reacting the first product with an effective C9 + Under transalkylation conditions, in the presence of 0 wt % or more hydrogen having a hydrogen / hydrocarbon molar ratio of 0-10, a hydrocarbon containing C9 + The feedstock of aromatic hydrocarbons and benzene is contacted with a second catalyst to make the C9 + Aromatic hydrocarbons are transalkylated and a second product containing xylene is produced. The method is mainly aimed at improving the transalkylation method, and the catalyst itself is not improved.
[0008] The current related technologies have problems such as low aromatic conversion efficiency and low xylene selectivity under liquid phase conditions. Therefore, a catalyst for transalkylation reaction is needed to improve xylene selectivity while reducing aromatic loss and by-product generation. Summary of the invention
[0009] The purpose of the present invention is to overcome the problems of low aromatic conversion rate and low xylene selectivity in liquid phase aromatic transalkylation reaction in the prior art, and to provide a catalyst containing Beta / Y composite molecular sieve, a preparation method and application thereof, and a method for liquid phase aromatic transalkylation. The catalyst is beneficial to promoting the liquid phase aromatic transalkylation reaction and has the characteristics of high aromatic conversion rate and high xylene selectivity.
[0010] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a catalyst containing Beta / Y composite molecular sieve, wherein the catalyst comprises Beta / Y composite molecular sieve and nickel, and the mass percentage of the Beta / Y composite molecular sieve is 95-99% based on the total amount of the catalyst, and the mass percentage of nickel is 1-5% based on nickel oxide.
[0011] Preferably, in the Beta / Y composite molecular sieve, the weight ratio of the Beta molecular sieve to the Y molecular sieve is 2-5:1, preferably 2-4:1.
[0012] A second aspect of the present invention provides a method for preparing a catalyst containing a Beta / Y composite molecular sieve, wherein the method comprises:
[0013] (1) mixing, molding and drying the Beta molecular sieve with an extrusion aid and a silicon-based binder to obtain a dry strip;
[0014] (2) subjecting the dried strips in step (1) to hydrothermal treatment in a solution containing an alkali source and an aluminum source to obtain a Beta / Y composite molecular sieve;
[0015] (3) impregnating the Beta / Y composite molecular sieve of step (2) in a solution containing a nickel precursor, and calcining to obtain a catalyst;
[0016] The catalyst comprises Beta / Y composite molecular sieve and nickel. Based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 95-99%, and based on nickel oxide, the mass percentage of nickel is 1-5%.
[0017] The third aspect of the present invention provides a catalyst containing Beta / Y composite molecular sieve prepared by the preparation method described in the second aspect.
[0018] The fourth aspect of the present invention provides an application of the catalyst containing the Beta / Y composite molecular sieve described in the first aspect or the third aspect in a liquid phase transalkylation reaction of aromatic hydrocarbons.
[0019] A fifth aspect of the present invention provides a method for liquid phase transalkylation of aromatic hydrocarbons, the method comprising: in the presence of hydrogen, under liquid phase reaction conditions, + The aromatic hydrocarbon mixture is contacted with a catalyst for reaction, and the catalyst is selected from the catalyst containing Beta / Y composite molecular sieve described in the first aspect or the third aspect.
[0020] Through the above technical solution, the beneficial effects obtained by the present invention are as follows:
[0021] The catalyst containing Beta / Y composite molecular sieve provided by the present invention uses Beta / Y composite molecular sieve as a carrier combined with active component nickel, which is beneficial to promoting the production of toluene and C9 + Aromatic materials undergo transalkylation reactions. Under liquid phase reaction conditions, the catalytic activity is high, with the characteristics of high aromatic conversion rate and high xylene selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the XRD spectrum of the Beta / Y composite molecular sieve in Example 1. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The first aspect of the present invention provides a catalyst containing Beta / Y composite molecular sieve, wherein the catalyst comprises Beta / Y composite molecular sieve and nickel, and the mass percentage of the Beta / Y composite molecular sieve is 95-99% based on the total amount of the catalyst, and the mass percentage of nickel is 1-5% based on nickel oxide.
[0025] In the present invention, the active component nickel is combined with the Beta / Y composite molecular sieve, and the active component nickel provides hydrogenation activity, which is beneficial to promote the hydrogenation of toluene and C9 + Aromatic materials undergo transalkylation reactions. Under liquid phase reaction conditions, the catalytic activity is high, with the characteristics of high aromatic conversion rate and high xylene selectivity.
[0026] In the present invention, the mass percentage of Beta / Y composite molecular sieve in the catalyst and the mass percentage of nickel in terms of nickel oxide are determined by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the testing instrument is Varian 725-ES series ICP-AES instrument.
[0027] According to the present invention, preferably, based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 97-99%, and based on nickel oxide, the mass percentage of nickel is 1-3%.
[0028] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on mass, unless the mass basis does not conform to the common understanding of those skilled in the art.
[0029] According to the present invention, preferably, the Beta / Y composite molecular sieve has a core-shell structure, including a core phase of a Beta molecular sieve and a shell layer of a Y molecular sieve. In the present invention, a layer of a Y molecular sieve is coated on the outside of the Beta molecular sieve, and the Y molecular sieve formed by in-situ crystallization has a certain proportion of mesoporous structure, a larger specific surface area, which is conducive to the diffusion of reaction molecules, faster access to the acid center active site, and further improves the catalytic activity.
[0030] According to the present invention, preferably, in the Beta / Y composite molecular sieve, the weight ratio of the Beta molecular sieve to the Y molecular sieve is 2-5: 1, such as 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1, 4.5: 1, 5: 1, or any range between the two, preferably 2-4: 1. In the present invention, the Beta / Y composite molecular sieve having the above weight ratio can make full use of the pores and acid center distribution characteristics of the two molecular sieves to achieve synergistic catalysis and improve the efficiency of the liquid phase transalkylation reaction.
[0031] In the present invention, the weight ratio of the Beta molecular sieve to the Y molecular sieve in the Beta / Y composite molecular sieve is measured by measuring the characteristic peak area ratio in the XRD spectrum.
[0032] According to the present invention, preferably, the average crystal size of the Beta / Y composite molecular sieve is less than 500nm, preferably 100-300nm. In the present invention, the particle size analysis of the Beta / Y composite molecular sieve is obtained by observation using an XL30E scanning electron microscope of Philips of the Netherlands. In the present invention, the Beta / Y composite molecular sieve has a small average crystal size, a large specific surface area, many active sites and is more accessible, and the prepared catalyst has high catalytic activity.
[0033] According to the present invention, preferably, the SiO2 / Al2O3 molar ratio of the Beta molecular sieve is 8-20, such as 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or any range between the two, preferably 10-15. In the present invention, the above-mentioned Beta molecular sieve is selected as the core phase of the composite molecular sieve. The SiO2 / Al2O3 molar ratio of the Beta molecular sieve is relatively low, the active sites are numerous, and it is easy to contact with the reacting molecules, thereby improving the liquid phase reaction diffusion rate.
[0034] In the present invention, the source of the Beta molecular sieve is not particularly limited, and it can be commercially available or prepared by existing methods, as long as the SiO2 / Al2O3 molar ratio of the Beta molecular sieve meets the above-defined range.
[0035] According to the present invention, preferably, the SiO2 / Al2O3 molar ratio of the Y molecular sieve is 4-10, such as 4, 5, 6, 7, 8, 9, 10, or any range between the two, preferably 5-8. In the present invention, the Y molecular sieve having the above SiO2 / Al2O3 molar ratio has a larger acid content, which helps to increase the active sites in the molecular sieve, and under the low temperature reaction conditions of the liquid phase, the catalyst can also have a higher activity, a high aromatic conversion rate, and a high xylene selectivity.
[0036] In the present invention, the SiO2 / Al2O3 molar ratio of the Y molecular sieve is measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES), and the testing instrument is: Varian 725-ES series ICP-AES instrument.
[0037] In the present invention, by Figure 1 It can be seen from the XRD spectrum of the Beta / Y composite molecular sieve that there are characteristic diffraction peaks of Beta and Y molecular sieves in the spectrum, which proves that Beta molecular sieve and Y molecular sieve exist in the Beta / Y composite molecular sieve.
[0038] A second aspect of the present invention provides a method for preparing a catalyst containing a Beta / Y composite molecular sieve, wherein the method comprises:
[0039] (1) mixing, molding and drying the Beta molecular sieve with an extrusion aid and a silicon-based binder to obtain a dry strip;
[0040] (2) subjecting the dried strips in step (1) to hydrothermal treatment in a solution containing an alkali source and an aluminum source to obtain a Beta / Y composite molecular sieve;
[0041] (3) impregnating the Beta / Y composite molecular sieve of step (2) in a solution containing a nickel precursor, and calcining to obtain a catalyst;
[0042] The catalyst comprises Beta / Y composite molecular sieve and nickel. Based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 95-99%, and based on nickel oxide, the mass percentage of nickel is 1-5%.
[0043] According to the present invention, preferably, based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 97-99%, and based on nickel oxide, the mass percentage of nickel is 1-3%.
[0044] According to the present invention, the types of the extrusion aids of the present invention are well known to those skilled in the art. Preferably, the extrusion aid is selected from at least one of sesbania powder, methylcellulose, hydroxypropyl methylcellulose and dextrin.
[0045] According to the present invention, the amount of the extrusion aid is not particularly limited, and those skilled in the art can make adaptive adjustments as needed to ensure that subsequent molding proceeds smoothly. Preferably, the amount of the extrusion aid is 3-10% of the weight of the Beta molecular sieve on a dry basis, preferably 5-8%.
[0046] In the present invention, the dry basis refers to the condition of roasting at 550°C for 3h.
[0047] According to the present invention, preferably, the silicon-based binder is silica sol and / or water glass, preferably silica sol.
[0048] According to the present invention, preferably, the amount of the silicon-based binder is 24-61%, preferably 30-61%, of the weight of the Beta molecular sieve on a dry basis, calculated as SiO2. In the present invention, the addition of the silicon-based binder can serve as a binder for mixing and molding in step (1) and can also provide a silicon source for the hydrothermal reaction in the subsequent step (2). No additional binder is required during the molding process of step (1).
[0049] In the present invention, the Beta molecular sieve, the extrusion aid, and the silicon-based binder are not particularly limited in the manner of adding, and they can be added separately or together.
[0050] According to a preferred embodiment of the present invention, the Beta molecular sieve and the extrusion aid are mixed evenly, and then the silicon-based binder is added and the mixing is continued.
[0051] The present invention has no specific limitation on the mixing conditions in step (1), which can be appropriately selected according to the specific situation, as long as the purpose of uniform mixing can be achieved. The equipment for the mixing is not particularly limited, and preferably, the mixing is carried out in a kneader.
[0052] The present invention has no particular limitation on the molding of step (1), and can be carried out according to conventional molding methods in the art. For example, it can be, but is not limited to, extrusion molding, spray molding or compression molding. In the present invention, extrusion molding is preferably used, and the specific method is well known to those skilled in the art, and will not be described in detail here.
[0053] According to a specific embodiment of the present invention, the mixture obtained in step (1) is first kneaded into a dough shape, and then extruded into a cylindrical strip shape.
[0054] The present invention has no particular limitation on the drying conditions, and can be appropriately selected according to the specific situation, as long as the purpose of drying can be achieved. Preferably, the drying conditions include: a temperature of 60-150° C. and a time of 3-12 hours.
[0055] According to the present invention, the type of the alkali source is not particularly limited, and it can be a conventional strong alkali. Preferably, the alkali source is sodium hydroxide and / or potassium hydroxide. In the present invention, when the silicon-based binder is silica sol, an additional alkali source is required, and the amount of the supplemented alkali source can be adaptively adjusted by those skilled in the art according to the preparation of the composite molecular sieve, and the composite molecular sieve structure can be obtained to meet the definition.
[0056] According to the present invention, the type of the aluminum source is not particularly limited, and is a conventional aluminum source for preparing molecular sieves in the art. Preferably, the aluminum source is selected from at least one of sodium aluminate, aluminum sulfate and aluminum nitrate.
[0057] In the present invention, the alkali source and the aluminum source are hydrothermally reacted with the formed carrier dry strips, and a layer of Y molecular sieve shell is coated on the surface of the Beta molecular sieve by in-situ growth. The coated Y molecular sieve shell has a mesoporous structure and a larger specific surface area, which is conducive to molecular diffusion and further improves the catalytic activity.
[0058] According to the present invention, preferably, in step (2), the silicon-based binder is calculated as SiO2, the alkali source is calculated as Na2O, and the aluminum source is calculated as Al2O3, and the molar ratio of the added amount of each substance satisfies n(SiO2):n(Al2O3):n(Na2O):n(H2O)=8-15:1:2.4-6:96-240, preferably 8-12:1:2.4-4.6:96-216. Adding the alkali source and the aluminum source according to the above molar ratio and dissolving them and then adding the carrier dry strips for hydrothermal reaction can produce a Y molecular sieve with a smaller SiO2 / Al2O3 molar ratio, increase the active sites in the molecular sieve, and produce a catalyst with high aromatic conversion rate and high xylene selectivity.
[0059] According to the present invention, preferably, the hydrothermal treatment conditions include: reaction temperature of 90-120°C, preferably 90-110°C; reaction time of 6-36h, preferably 12-24h. In the present invention, the hydrothermal reaction is carried out under the above conditions, and the hydrothermal reaction can be static or dynamic, but the stirring paddle cannot touch the formed carrier during dynamic hydrothermal treatment. Reasonable control of the material ratio and hydrothermal treatment conditions can prevent the generation of other impurity crystalline phases during the crystal transformation process.
[0060] In the present invention, there is no particular limitation on the equipment for the hydrothermal reaction, as long as the reaction can be carried out under the hydrothermal reaction conditions, and those skilled in the art can select it according to their needs.
[0061] In the present invention, after the hydrothermal treatment, the steps of cooling and filtering are also included. The cooling and filtering methods are not particularly limited and are conventional cooling and filtering methods in the art.
[0062] According to the present invention, preferably, the method further comprises, in step (3), exchanging the Beta / Y composite molecular sieve with ammonia, and then performing the impregnation. In the present invention, the ammonia exchange conditions are not particularly limited, and those skilled in the art can select conventional ammonia exchange conditions to exchange the Beta / Y composite molecular sieve into an ammonia type.
[0063] In the present invention, the impregnation conditions are not particularly limited, and those skilled in the art can select conventional impregnation conditions. Preferably, the present invention adopts an equal volume impregnation method.
[0064] According to the present invention, the type of the nickel precursor is not particularly limited, and is a conventional soluble nickel salt in the art. Preferably, the nickel precursor is nickel nitrate and / or nickel acetate.
[0065] According to the present invention, preferably, in the solution containing the nickel precursor, the mass concentration of nickel is 1.5-5wt%, preferably 1.8-4wt%.
[0066] In the present invention, the mass ratio of the Beta / Y composite molecular sieve to the solution containing the nickel precursor is not particularly limited, so that the mass percentage of nickel in the final catalyst calculated as nickel oxide meets the limit, and those skilled in the art can adaptively adjust it according to the loading condition of the active component nickel.
[0067] The present invention has no particular limitation on the calcination conditions, and the calcination can be carried out according to conventional methods in the art. The calcination is generally carried out in an air atmosphere, and the air atmosphere includes a flowing atmosphere or a static atmosphere. According to the present invention, preferably, the calcination conditions include: a temperature of 450-650°C, preferably 500-600°C; and a time of 2-10h, preferably 3-8h.
[0068] The third aspect of the present invention provides a catalyst containing Beta / Y composite molecular sieve prepared by the preparation method described in the second aspect.
[0069] The fourth aspect of the present invention provides an application of the catalyst containing the Beta / Y composite molecular sieve described in the first aspect or the third aspect in a liquid phase transalkylation reaction of aromatic hydrocarbons.
[0070] A fifth aspect of the present invention provides a method for liquid phase transalkylation of aromatic hydrocarbons, the method comprising: in the presence of hydrogen, under liquid phase reaction conditions, + The aromatic hydrocarbon mixture is contacted with a catalyst for reaction, and the catalyst is selected from the catalyst containing Beta / Y composite molecular sieve described in the first aspect or the third aspect.
[0071] According to the present invention, preferably, the liquid phase reaction conditions include: temperature of 200-350°C, preferably 250-300°C; pressure of 2-5MPa, preferably 3-4MPa; mass space velocity of 0.5-2.5h -1 , preferably 1-2h -1 .
[0072] The "in the presence of hydrogen" mentioned in the present invention is a conventional choice in the art. Various hydrogen-containing gases can be used to implement the present invention, as long as the amount of hydrogen in the hydrogen-containing gas can meet the requirements of the present invention for the production of toluene and C9 + The conditions for liquid phase reaction of the aromatic hydrocarbon mixture are sufficient. The present invention has no specific requirements for this and will not be described in detail herein.
[0073] In the present invention, the toluene and C9 + Toluene and C9 in aromatic hydrocarbon mixture + The content range of aromatics is relatively wide, and those skilled in the art can make adaptive adjustments according to the conditions of the liquid phase reaction. Preferably, the weight content of toluene in the mixture is 30-70%, and the C9 + The weight content of aromatic hydrocarbons is 30-70%.
[0074] The present invention is to C9 + The range of aromatic hydrocarbons is relatively wide, and any aromatic hydrocarbon that can be mixed with toluene to undergo a liquid phase reaction to generate xylene is sufficient. + The aromatic hydrocarbon is at least one selected from aromatic hydrocarbons having 9 or more carbon atoms.
[0075] In the present invention, a gas chromatograph is used to measure the content of aromatic hydrocarbons, and the testing instrument is: Agilent Technologies 7890A GC System.
[0076] According to a particularly preferred embodiment of the present invention, a method for preparing a catalyst containing Beta / Y composite molecular sieve comprises:
[0077] (1) mixing, molding and drying the Beta molecular sieve with an extrusion aid and a silicon-based binder to obtain a dry strip;
[0078] (2) subjecting the dried strips in step (1) to hydrothermal treatment in a solution containing an alkali source and an aluminum source to obtain a Beta / Y composite molecular sieve;
[0079] (3) impregnating the Beta / Y composite molecular sieve of step (2) in a solution containing a nickel precursor, and calcining to obtain a catalyst;
[0080] The catalyst comprises a Beta / Y composite molecular sieve and nickel. Based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 97-99%, and based on nickel oxide, the mass percentage of nickel is 1-3%;
[0081] In step (2), the silicon-based binder is calculated as SiO2, the alkali source is calculated as Na2O, and the aluminum source is calculated as Al2O3, and the molar ratio of the added amount of each substance satisfies n(SiO2):n(Al2O3):n(Na2O):n(H2O)=8-12:1:2.4-4.6:96-216;
[0082] The hydrothermal treatment conditions include: reaction temperature of 90-110° C.; reaction time of 12-24 h.
[0083] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples,
[0084] The aromatics conversion is defined as follows:
[0085]
[0086] The xylene selectivity is defined as follows:
[0087]
[0088] The test methods for the Beta / Y composite molecular sieve and the mass percentage of nickel in terms of nickel oxide in the catalyst, the weight ratio of Beta molecular sieve and Y molecular sieve in the Beta / Y composite molecular sieve, the average crystal size, the SiO2 / Al2O3 molar ratio of the Beta molecular sieve, and the SiO2 / Al2O3 molar ratio of the Y molecular sieve are described in the aforementioned specification and will not be repeated here;
[0089] Unless otherwise specified, all reagents and materials used were commercially available, and the room temperature was 25°C.
[0090] Example 1
[0091] 65g of dry basis Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4g of sesbania powder were mixed uniformly in a kneader, 99g of silica sol (containing 40wt% SiO2) was added, kneaded for 30-40 minutes to obtain a dough, extruded through a die into a cylindrical strip with a diameter of 1.7mm and a length of 2.0mm, and dried at 120°C for 6h. The dried strip was placed in a solution containing 12g of sodium hydroxide (96wt% NaOH), 20.5g of sodium aluminate (41wt% Al2O3, 26wt% Na2O), and 178g of water, and hydrothermally treated at 110°C for 16h, filtered out the liquid after cooling, and conventionally exchanged into an ammonia type, dried at 120°C for 6h, and the carrier was immersed in an aqueous solution containing 7.8g of nickel nitrate in equal volume, and then dried at 120°C and calcined at 550°C in air atmosphere for 4h to obtain catalyst A, as shown in Table 1.
[0092] Figure 1 is the XRD spectrum of the Beta / Y composite molecular sieve of Example 1. Figure 1 It can be seen that the Beta / Y composite molecular sieve contains characteristic diffraction peaks of both Beta molecular sieve and Y molecular sieve.
[0093] Example 2
[0094] 73.5 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4.4 g of sesbania powder were mixed uniformly in a kneader, 73.5 g of silica sol (containing 40 wt% SiO2) was added, and kneaded for 30-40 minutes to obtain a dough-like shape, which was extruded through a die into a cylindrical strip with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 hours. The dried strip was placed in a solution containing 8.9 g of sodium hydroxide (96 wt% NaOH), 15.2 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 132 g of water, and hydrothermally treated at 110°C for 16 hours, and after cooling, the liquid was filtered out and conventionally exchanged into an ammonia type, and dried at 120°C for 6 hours. The carrier was immersed in an aqueous solution containing 7.8 g of nickel nitrate in equal volume, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 hours to obtain catalyst B, as shown in Table 1.
[0095] Example 3
[0096] 78.4 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4.7 g of sesbania powder were mixed evenly in a kneader, 58.5 g of silica sol (containing 40 wt% SiO2) and 20 g of water were added, and the mixture was kneaded for 30-40 minutes to obtain a dough-like shape, which was extruded through a die into cylindrical strips with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 h. The dried strips were placed in a solution containing 7.1 g of sodium hydroxide (96 wt% NaOH), 12.2 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 106 g of water, and hydrothermally treated at 110°C for 16 h, and the liquid was filtered out after cooling and conventionally exchanged into an ammonia type, and dried at 120°C for 6 h. The carrier was immersed in an aqueous solution containing 7.8 g of nickel nitrate in equal volume, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 h to obtain catalyst C, as shown in Table 1.
[0097] Example 4
[0098] 81.7 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 5 g of sesbania powder were mixed uniformly in a kneader, 49 g of silica sol (containing 40 wt% SiO2) was added, 30 g of water was added, and the mixture was kneaded for 30-40 minutes to obtain a dough-like shape, which was extruded through a die into a cylindrical strip with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 h. The dried strip was placed in a solution containing 5.9 g of sodium hydroxide (96 wt% NaOH), 10.1 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 88 g of water, and hydrothermally treated at 110°C for 16 h, and after cooling, the liquid was filtered off and conventionally exchanged into an ammonia type, and dried at 120°C for 6 h. The carrier was immersed in an aqueous solution containing 7.8 g of nickel nitrate in equal volume, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 h to obtain catalyst D, as shown in Table 1.
[0099] Example 5
[0100] 72.8 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4 g of sesbania powder were mixed evenly in a kneader, 72.8 g of silica sol (containing 40 wt% SiO2) was added, kneaded for 30-40 minutes to obtain a dough, extruded through a die into a cylindrical strip with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 hours. The dry strip was placed in a solution containing 8.8 g of sodium hydroxide (96 wt% NaOH), 15 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 130 g of water, and hydrothermally treated at 110°C for 16 hours, filtered out the liquid after cooling, and conventionally exchanged into an ammonia type, dried at 120°C for 6 hours, and the carrier was immersed in an aqueous solution containing 11.7 g of nickel nitrate in equal volume, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 hours to obtain catalyst E, as shown in Table 1.
[0101] Example 6
[0102] 72g of dry basis Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4.3g of sesbania powder were mixed evenly in a kneader, 72g of silica sol (containing 40wt% SiO2) was added, kneaded for 30-40 minutes to obtain a dough, extruded through a die into a cylindrical strip with a diameter of 1.7mm and a length of 2.0mm, and dried at 120℃ for 6h. The dry strip was placed in a solution containing 8.7g of sodium hydroxide (96wt% NaOH), 14.9g of sodium aluminate (41wt% Al2O3, 26wt% Na2O), and 130g of water, and hydrothermally treated at 110℃ for 16h, filtered out the liquid after cooling, and conventionally exchanged into an ammonia type, and dried at 120℃ for 6h. The carrier was impregnated with an equal volume of an aqueous solution containing 15.6g of nickel nitrate, and then dried at 120℃ and calcined at 550℃ in air atmosphere for 4h to obtain catalyst F, as shown in Table 1.
[0103] Example 7
[0104] 73.5 g of dry basis Beta molecular sieve (SiO2 / Al2O3 molar ratio is 20) and 4.4 g of sesbania powder were mixed uniformly in a kneader, 73.5 g of silica sol (containing 40 wt% SiO2) was added, and kneaded for 30-40 minutes to obtain a dough-like state, which was extruded through a die into cylindrical strips with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 h. The dried strips were placed in a solution containing 8.9 g of sodium hydroxide (96 wt% NaOH), 15.2 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 132 g of water, and hydrothermally treated at 110°C for 16 h. After cooling, the liquid was filtered out and conventionally exchanged into an ammonia type, and dried at 120°C for 6 h. An equal volume of the carrier was immersed in an aqueous solution containing 7.8 g of nickel nitrate, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 h to obtain catalyst G, as shown in Table 1.
[0105] Example 8
[0106] 73.5 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4.4 g of sesbania powder were mixed uniformly in a kneader, 78.7 g of silica sol (containing 40 wt% SiO2) was added, and the mixture was kneaded for 30-40 minutes to obtain a dough-like shape, which was extruded through a die into cylindrical strips with a diameter of 1.7 mm and a length of 2.0 mm. The strips were dried at 120°C for 6 h, and the dried strips were placed in a solution containing 10 g of sodium hydroxide (96 wt% NaOH), 8.7 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 142 g of water, and hydrothermally treated at 110°C for 16 h. After cooling, the liquid was filtered out and conventionally exchanged into an ammonia type, and dried at 120°C for 6 h. An equal volume of the carrier was impregnated in an aqueous solution containing 7.8 g of nickel nitrate, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 h to obtain catalyst H, as shown in Table 1.
[0107] Example 9
[0108] 73.5 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4.4 g of sesbania powder were mixed uniformly in a kneader, 73.5 g of silica sol (containing 40 wt% SiO2) was added, and the mixture was kneaded for 30-40 minutes to obtain a dough-like shape, which was extruded through a die into cylindrical strips with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 h. The dried strips were placed in a solution containing 7 g of sodium hydroxide (96 wt% NaOH), 15.2 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 132 g of water, and hydrothermally treated at 120°C for 24 h. After cooling, the liquid was filtered out and conventionally exchanged into an ammonia type, and dried at 120°C for 6 h. An equal volume of the carrier was immersed in an aqueous solution containing 7.8 g of nickel nitrate, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 h to obtain Catalyst I, as shown in Table 1.
[0109] Comparative Example 1
[0110] 67.5 g Beta (SiO2 / Al2O3 molar ratio of 10) on a dry basis, 22.5 g HY molecular sieve (SiO2 / Al2O3 molar ratio of 5) on a dry basis, 10 g alumina on a dry basis, and 4 g sesbania powder were mixed uniformly in a kneader, 45 g of an aqueous solution containing 0.5 g nitric acid was slowly added into the kneader, and the mixture was kneaded for 30 minutes to obtain a dough-like shape, which was extruded through a die into cylindrical strips with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 h. An equal volume of the carrier was immersed in an aqueous solution containing 7.8 g nickel nitrate, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 h to obtain a catalyst, as shown in Table 1.
[0111] Comparative Example 2
[0112] 73.5 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio of 10) and 4.4 g of sesbania powder were mixed uniformly in a kneader, 73.5 g of silica sol (containing 40 wt% SiO2) was added, and the mixture was kneaded for 30-40 minutes to obtain a dough-like shape, which was extruded through a die into cylindrical strips with a diameter of 1.7 mm and a length of 2.0 mm, and dried at 120°C for 6 h. The dried strips were placed in a solution containing 8.9 g of sodium hydroxide (96 wt% NaOH), 15.2 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O), and 132 g of water, and hydrothermally treated at 110°C for 16 h. After cooling, the liquid was filtered out and conventionally exchanged into an ammonia type, and dried at 120°C for 6 h. An equal volume of the carrier was immersed in an aqueous solution containing 10.6 g of magnesium nitrate, and then dried at 120°C and calcined at 550°C in air atmosphere for 4 h to obtain a catalyst, as shown in Table 1.
[0113] Comparative Example 3
[0114] 8.9 g of sodium hydroxide (96 wt% NaOH) and 15.2 g of sodium aluminate (41 wt% Al2O3, 26 wt% Na2O) were dissolved in 88 g of water, and 73.3 g of silica sol was added. After stirring, 73.5 g of Beta molecular sieve (SiO2 / Al2O3 molar ratio is 10) was added on a dry basis, and the mixture was hydrothermally treated at 110°C for 16 h. After filtering, exchanging, washing and drying, the mixture was added to a kneader and mixed with 5 g of sesbania powder. Then 43.2 g of silica sol (containing 40 wt% SiO2) was added. The mixture was hydrated and kneaded for 30-40 minutes to obtain a dough-like dough. The dough was extruded through a die into cylindrical strips with a diameter of 1.7 mm and a length of 2.0 mm. The dough was dried at 120°C for 6 h. An equal volume of the carrier was immersed in an aqueous solution containing 9.2 g of nickel nitrate. The catalyst was obtained after drying at 120°C and calcined at 550°C in air atmosphere for 4 h. See Table 1 for details.
[0115] Table 1
[0116]
[0117] Test Case
[0118] The catalysts prepared in the examples and comparative examples were respectively loaded into a fixed bed reactor and heated at a temperature of 275°C, a pressure of 3.5 MPa, and a space velocity of 1.5 h -1 , liquid phase transalkylation reaction was carried out under hydrogen atmosphere conditions. The raw material composition is shown in Table 2, and the reaction results are listed in Table 3.
[0119] Table 2
[0120] Components Toluene <![CDATA[C9 Aromatics]]> <![CDATA[C 10 Aromatics]]> Mass content, % 50 45 5
[0121] Table 3
[0122] catalyst Aromatic conversion rate, % Xylene selectivity, % A 47.8 83.9 B 48.3 85.2 C 47.1 84.6 D 46.5 81.8 E 49.0 82.1 F 49.2 80.0 G 46.5 83.6 H 46.7 83.4 I 47.6 85.1 Comparative Example 1 34.3 70.1 Comparative Example 2 35.8 68.2 Comparative Example 3 30.9 72.3
[0123] The catalysts prepared in the examples and comparative examples were respectively loaded into a fixed bed reactor and heated at a temperature of 290°C, a pressure of 4.0 MPa, and a space velocity of 1.0 h -1 , liquid phase transalkylation reaction was carried out under hydrogen atmosphere conditions. The raw material composition is shown in Table 2, and the reaction results are listed in Table 4.
[0124] Table 4
[0125] catalyst Aromatic conversion rate, % Xylene selectivity, % A 48.2 83.5 B 49.0 84.8 C 47.8 84.2 D 47.0 81.2 E 49.3 80.8 F 49.6 79.5 G 47.1 83.1 H 47.2 82.9 I 48.2 84.5 Comparative Example 1 35.0 69.2 Comparative Example 2 36.1 67.0 Comparative Example 3 31.2 72.0
[0126] It can be seen from the results in Table 3 and Table 4 that the catalyst containing the Beta / Y composite molecular sieve provided by the present invention has a higher aromatic conversion rate and a higher xylene selectivity under liquid phase reaction conditions by combining the Beta / Y composite molecular sieve with a specific structure and a nickel active component, and can be used in the industrial production of p-xylene to achieve the purpose of increasing the production of xylene.
[0127] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst containing Beta / Y composite molecular sieve, characterized in that: The catalyst comprises Beta / Y composite molecular sieve and nickel. Based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 95-99%, and based on nickel oxide, the mass percentage of nickel is 1-5%.
2. The catalyst according to claim 1, wherein Based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 97-99%, and the mass percentage of nickel is 1-3% based on nickel oxide; Preferably, the Beta / Y composite molecular sieve has a core-shell structure, including a Beta molecular sieve in the core phase and a Y molecular sieve in the shell layer; Preferably, in the Beta / Y composite molecular sieve, the weight ratio of Beta molecular sieve to Y molecular sieve is 2-5:1, preferably 2-4:1; Preferably, the average crystal size of the Beta / Y composite molecular sieve is less than 500 nm, preferably 100-300 nm.
3. The catalyst according to claim 2, wherein The SiO2 / Al2O3 molar ratio of the Beta molecular sieve is 8-20, preferably 10-15; Preferably, the SiO2 / Al2O3 molar ratio of the Y molecular sieve is 4-10, preferably 5-8.
4. A method for preparing a catalyst containing Beta / Y composite molecular sieve, characterized in that: The method comprises: (1) mixing, molding and drying the Beta molecular sieve with an extrusion aid and a silicon-based binder to obtain a dry strip; (2) subjecting the dried strips in step (1) to hydrothermal treatment in a solution containing an alkali source and an aluminum source to obtain a Beta / Y composite molecular sieve; (3) impregnating the Beta / Y composite molecular sieve of step (2) in a solution containing a nickel precursor, and calcining to obtain a catalyst; The catalyst comprises Beta / Y composite molecular sieve and nickel. Based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 95-99%, and based on nickel oxide, the mass percentage of nickel is 1-5%.
5. The preparation method according to claim 4, wherein Based on the total amount of the catalyst, the mass percentage of the Beta / Y composite molecular sieve is 97-99%, and the mass percentage of nickel is 1-3% based on nickel oxide; Preferably, the extrusion aid is selected from at least one of sesbania powder, methylcellulose, hydroxypropyl methylcellulose and dextrin; Preferably, the amount of the extrusion aid is 3-10%, preferably 5-8%, of the weight of the Beta molecular sieve on a dry basis; Preferably, the silicon-based binder is silica sol and / or water glass; Preferably, the amount of the silicon-based binder used is 24-61%, preferably 30-61%, of the weight of the Beta molecular sieve on a dry basis, calculated as SiO2.
6. The preparation method according to claim 4 or 5, wherein: The alkali source is sodium hydroxide and / or potassium hydroxide; Preferably, the aluminum source is selected from at least one of sodium aluminate, aluminum sulfate and aluminum nitrate; Preferably, in step (2), the silicon-based binder is calculated as SiO2, the alkali source is calculated as Na2O, and the aluminum source is calculated as Al2O3, and the molar ratio of the added amount of each substance satisfies n(SiO2):n(Al2O3):n(Na2O):n(H2O)=8-15:1:2.4-6:96-240, preferably 8-12:1:2.4-4.6:96-216; Preferably, the hydrothermal treatment conditions include: reaction temperature of 90-120°C, preferably 90-110°C; reaction time of 6-36h, preferably 12-24h.
7. The preparation method according to any one of claims 4 to 6, wherein: The method further comprises, in step (3), exchanging the Beta / Y composite molecular sieve with ammonia and then performing the impregnation; Preferably, the nickel precursor is nickel nitrate and / or nickel acetate; And / or, in the solution containing the nickel precursor, the mass concentration of nickel is 1.5-5wt%, preferably 1.8-4wt%; And / or, the calcination conditions include: temperature of 450-650° C., preferably 500-600° C.; time of 2-10 h, preferably 3-8 h.
8. A catalyst containing Beta / Y composite molecular sieve obtained according to the preparation method according to any one of claims 4 to 7.
9. Use of the catalyst containing Beta / Y composite molecular sieve according to any one of claims 1 to 3 and 8 in liquid phase transalkylation of aromatic hydrocarbons.
10. A method for liquid phase transalkylation of aromatic hydrocarbons, the method comprising: In the presence of hydrogen, under liquid phase reaction conditions, a mixture containing toluene and C9 + The aromatic hydrocarbon mixture is contacted with a catalyst for reaction, wherein the catalyst is selected from the catalyst containing Beta / Y composite molecular sieve according to any one of claims 1 to 3 and 8; Preferably, the liquid phase reaction conditions include: temperature of 200-350°C, preferably 250-300°C; pressure of 2-5MPa, preferably 3-4MPa; mass space velocity of 0.5-2.5h -1 , preferably 1-2h -1 .
Citation Information
Patent Citations
Liquid phase transalkylation process
CN108779047A
Transalkylation of heavy aromatic hydrocarbons
CN109790084A
Disproportionation and transalkylation of heavy aromatic hydrocarbons
CN109803944A
Catalyst for aromatics alkyl transferring and dealkylation to synthesis benzene and xylene
CN101121144A
Toluene disproportionation and alkyl transfer catalyst and preparation method thereof
CN101898152A